The Relationship Arm Muscle Strength and Leg Muscle Strength with Results of 50 Meter Freestyle Swimming Speed - El Tsaurah Qori, Raaidatu; Surisman; Joan, Joan Siswoyo; Lungit, Lungit Wicaksono (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The purpose of this study was to determine the relationship arm muscle strength and leg muscle strength in swimming speed of 50 meters in Club Swimmer Tirta Kartika. The method used in this research is correlational description. The samples used were 30 athletes. Sampling using total sampling technique. Data analysis using product moment correlation. The results of data analysis show that (1) the relationship between arm muscle strength and the results of the 50 meter freestyle swimming speed on male athletes of rx1.y = 0.852 > r(0,05)(13) = 0,441 and on female athletes of rx1.y = 0.954 > r(0,05)(13) = 0,441 (2) the relationship between leg muscle strength and the 50 meter freestyle swimming speed on male athletes of rx2.y = 0.856 > r(0,05)(13) = 0,441 and on female athletes of rx2.y = 0.975 > r(0,05)(13)= 0,441 (3) the relationship between arm muscle strength and strength leg muscles with a 50 meter freestyle swimming speed on male athletes of rx1.x2.y = 0.856 > r(0,05)(13)= 0,441 and on famele athletes of rx1.x2.y = 0.978 > r(0,05)(13)= 0,441. The conclusion of this study is that there is a relationship arm muscle strength and leg muscle strength in swimming speed of 50 meters in Club Swimmer Tirta Kartika.